PERCEIVED EFFECTS OF MICROFINANCE ON WOMEN EMPOWERMENT IN LANKWANTANANG-MADINA MUNICIPALITY - Ayam, J.; Abangbase, F.; Dadzie, E. N. (UDS International Journal of Development, 2021)
This paper examines the impact of microfinance on women empowerment through a cross-sectional survey with a total of 189 respondents in La-Nkwantanang municipality. Paired sample t-test was performed to analyse the situation before and after joining Microfinance Institutions (MFIs) to access credit facilities. Women empowerment is measured using three indicators namely: standard of living; generation of income from business operation; and participation in decision making at the family level. The main effects of microfinance services computed using the summated scale were found to suggest an improved standard of living with an average mean score of 1.5234 and standard deviation of 0.84099, improvement in business operations with a score of 1.4769 and standard deviation of 0.98718 and enhanced participation of women in decision making with a mean of 1.38378 and standard deviation of 0.98287. The paired sample test results indicated a p-value of 0.000 which is less than 5% (p<0.05). This study confirms the view that access to micro credit after joining MFIs, increased participants’ incomes and savings, improved their standard of living and increased their participation in decision making within the family. Based on the findings, it is recommended that MFIs should expand their financial advisory services to ensure the prudent utilisation of micro credit. Government must design appropriate micro credit policies that support this expansion. Keywords: Microfinance, Women Empowerment, Survey, Ghana